How to communicate with patients in written asynchronous online conversations: an intervention study with undergraduate medical students in a cross-over design - Festl-Wietek, Teresa; Erschens, Rebecca; Griewatz, Jan; Zipfel, Stephan; Herrmann-Werner, Anne (Frontiers in Medicine, 2023)
Introduction The patient-physician encounter is the core element in the treatment of patients and the diagnosis of disease. In these times of digitalization, patient-physician communication is increasingly taking place online: patients embrace new possibilities offered digitally, and physicians are encouraged to adapt accordingly. Since a huge part of online communication is written, this study aims to investigate how medical students communicate with patients online by focusing on their written competencies and whether an intervention might improve their competencies. Methods This study was performed in an explanatory cross-sectional manner with a cross-over design. Second-year medical students participated. An intervention was developed on how to formulate an appropriate written response to a patient’s request and integrated a longitudinal communication class. The intervention consists of education on general set-up (e.g., greetings), syntax, spelling, content and kind of communication (e.g., appreciative attitude). After meeting a patient in a simulated role play medical students received the patient’s request via a digital platform. The control group had the same simulated role play and the same task but they received the intervention on communication afterwards. Intervention and control group were statistically compared based on a checklist. Results Twenty-nine medical students took part in the study. The results showed that the medical students had basic competencies in dealing with written communication independent if they received the intervention (CG: M = 3.86 ± 1.23 vs. IG: M = 4.07 ± 1.03; p = 0.625). Similar results were also for the emotional competency ratings (MCG = 3.36 ± 1.08; MIG = 3.67 ± 0.98; p = 0.425).The intervention was able to lead to a more appreciative response toward patient. Discussion Intervention on basic competencies such as simple language and clear presentation might not be needed as an integral part in medical education. However, medical students should learn how to present empathic and authentic behavior in written online communication.